Remote Sensing Assessment Of Land Cover/Land Use Changes And Its Relationship On Land Surface Temperature In Penang Island - Tan , Kok Chooi (2010)
Land surface temperature (LST) plays an important role in local, regional and global climate studies. LST controls the distribution of the budget for radiation heat between the atmosphere and the Earth’s surface. Therefore, it is important to evaluate abrupt changes in land use/land cover (LULC). Penang Island, Malaysia has been experiencing a rapid and drastic change in urban expansion over the past two decades due to growth in industrial and residential areas. The aim of this study was to investigate and evaluate the impact of LST with respect to land-use changes in Penang Island, Malaysia.